2021
DOI: 10.1016/j.ygyno.2020.10.037
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a Facebook campaign among mothers on HPV vaccine uptake among their daughters: A randomized field study

Abstract: A large randomized controlled study on the effectiveness of Facebook campaigns on the uptake of HPV immunizations. • The campaign aimed a potential target population of 17,271 mothers to 14 year-old daughters. • In families of low SES, our campaign reduced uptake by 10% while in low-medium level, it increased the uptake by 6%. • HPV promotion campaign in social media might be a double-edged sword depending on target population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 25 publications
0
40
0
1
Order By: Relevance
“…This is an important indicator because of the focus on collaboration and communication between multiple levels of an organization which can increase the overall impact of the intervention and the probability of the behavior being adopted and/or In the implementation dimension, we were interested in intervention studies that incorporated social media technology to deliver the intervention. Although the authors did not evaluate whether using a specific social media type was effective in delivering the intervention, based on our review we found that interventions that utilized Facebook [41,50] and text messages [15,45,49] reported significant improvements in HPV vaccination. The most frequent technology used was text messaging [15,37,39,43,[45][46][47][48][49].…”
Section: Adoption Dimensionmentioning
confidence: 89%
See 2 more Smart Citations
“…This is an important indicator because of the focus on collaboration and communication between multiple levels of an organization which can increase the overall impact of the intervention and the probability of the behavior being adopted and/or In the implementation dimension, we were interested in intervention studies that incorporated social media technology to deliver the intervention. Although the authors did not evaluate whether using a specific social media type was effective in delivering the intervention, based on our review we found that interventions that utilized Facebook [41,50] and text messages [15,45,49] reported significant improvements in HPV vaccination. The most frequent technology used was text messaging [15,37,39,43,[45][46][47][48][49].…”
Section: Adoption Dimensionmentioning
confidence: 89%
“…The most frequent technology used was text messaging [15,37,39,43,[45][46][47][48][49]. Additionally, only eight articles reported the underlying theoretical framework used in intervention development [38,39,41,42,[49][50][51][52]. Theories provide a systematic view of phenomena by specifying the relationship between program inputs (resources), program activities (how the program is implemented), and their outputs or outcomes [61][62][63].…”
Section: Adoption Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian (Dehghani & Tumer, 2015), (E.B, 2016), (Pancaningrum & Rahayu, 2017), (Tikno, 2017), (M.S et al, 2018), (Wiese et al, 2020), (S. Huang et al, 2020), (Chodick et al, 2020), (Chierici et al, 2019) menyatakan bahwa Facebook Ads berpengaruh terhadap peningkatan brand awareness. Sebaliknya, menurut hasil penelitian (Vries et al, 2017), (Sung et al, 2020), menyatakan bahwa Facebook Ads tidak efektif dalam meningkatkan brand awareness.…”
Section: Bertinus Sijabatunclassified
“…The discordance between social media platforms used by clinicians versus patients is only one of many factors. A randomized study that used Facebook to promote medical information to increase uptake of HPV vaccination reported no difference in the targeted and non-targeted groups, despite more than 1.8 million advertisements and information posts being promoted on Facebook during the study period 6 . Pregnant women and new mothers are targeted by anti-vaccination advocates using social media platforms to disseminate mis-information.…”
mentioning
confidence: 99%